CONFABULATIONS IN A CHRONIC ALCOHOLIC- A SUBTLE PRESENTATION OF KORSAKOFF SYNDROME - Leyfman, Yan (International Journal of Research -GRANTHAALAYAH, 2019)
Wernicke Encephalopathy is an acute neuropsychiatric condition, characterized by confusion, nystagmus, ataxia, and ophthalmoplegia, resulting from thiamine (Vitamin B1) deficiency, typically secondary to alcohol abuse. Failure to properly diagnose, which occurs in 80% of the time, can result in gradual progression to irreversible Korsakoff Syndrome, characterized by irreversible personality changes, and anterograde and retrograde amnesia. The present case report seeks to highlight this patient’s chronology to Korsakoff Syndrome and our attempted interventions.